Dynamically reconfigurable acoustofluidic metasurface for subwavelength particle manipulation and assembly - Sushruta Surappa; Suraj Pavagada; Fernando Soto; Demir Akin; Charles Wei; F. Levent Degertekin; Utkan Demirci (Nature Communications)
Abstract Particle manipulation plays a pivotal role in scientific and technological domains such as materials science, physics, and the life sciences. Here, we present a dynamically reconfigurable acoustofluidic metasurface that enables precise trapping and positioning of microscale particles in fluidic environments. By harnessing acoustic-structure interaction in a passive membrane resonator array, we generate localized standing acoustic waves that can be reconfigured in real-time. The resulting radiation force allows for subwavelength manipulation and patterning of particles on the metasurface at individual and collective scales, with actuation frequencies below 2 MHz. We further demonstrate the capabilities of the reconfigurable metasurface in trapping and enriching beads and biological cells flowing in microfluidic channels, showcasing its potential in high-throughput bioanalytical applications. Our versatile and biocompatible particle manipulation platform is suitable for applications ranging from the assembly of colloidal particles to enrichment of rare cells.